2005
DOI: 10.17221/5599-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A macroscopical investigation of the portal veins of the Van cat

Abstract: In this study veins that constituted the portal vein were investigated in eight adult Van cats. The portal vein of the Van cat was composed of five peripheral branches which supplied the abdominal organs and two intrahepatic branches at the hepatic porta. The peripheral branches were cranial mesenteric, splenic, gastroduodenal, right gastric and cystic veins. The cranial mesenteric vein was the largest vessel that joined to the portal vein, and was constituted by the caudal pancreaticoduodenal, ileal, ileocoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…A study of Van cat showed that the portal vein formed to the caudal and cranial pancreaticoduodenal vein (right lobe drain), and open into the caudal mesenteric vein. The findings from the present study were similar to those reported previously (17). The caudal mesenteric vein emptied into the cranial mesenteric vein (18 animals), or into the splenic vein (2 animals).…”
Section: Resultssupporting
confidence: 92%
“…A study of Van cat showed that the portal vein formed to the caudal and cranial pancreaticoduodenal vein (right lobe drain), and open into the caudal mesenteric vein. The findings from the present study were similar to those reported previously (17). The caudal mesenteric vein emptied into the cranial mesenteric vein (18 animals), or into the splenic vein (2 animals).…”
Section: Resultssupporting
confidence: 92%